PERAN SUPERVISI PENGAWAS MEMODERASI PENGARUH PENDIDIKAN DAN PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU (Studi Kasus pada Guru-guru Sekolah Dasar di UPT Dinas pendidikan Kecamatan Pamotan Kabupaten Rembang) (Jurnal Mahasiswa Pasca Sarjana, 2014)
Obyective of this research is to examine the supervision, moderate the influence of education and workshop and work motivation toward teachers work. Case Study Over teachers of Elementary School in UPT Education Departement of Pamotan Subdistrict Rembang District. The population of research are two hundreds and four teachers of Elementary School in Pamotan Subdistrict. By using Slovin reasonable sample, one hundred and trrty five teacher’s respondent who are differentiated based on room category in each shool superintenden’s construction area. Primary data is taken on January 2014. Data collecting by using questioner, after data is collected, it is processed by using SPSS 19 computer Proram. Validity test and reliability  questioner is explained valid LF > 0,4 and relaibel with Cronbach Alpha > 0,7. F tes and t test, each of them signification 0,05 which is explained fit and independent variable influence significant. The result of this research shws that 1) Trainning has no influence toward teacher’s work significantly. 2) Work motivation has no influence of teacher’s work.  3) Supervision Supervisor significantly no influence effect on the of teacher’s work. 4) Supervision moderating significantly has no effect on the performance of the teacher training. 5) Superintendent Supervision  weaken the influence of work motivation to ward teacher’s work. Keyword. : Trainning, Motivation, Supervision, Perfoance, Moderation and influence